A Prudential Assessment of Islamic Banking System and Sharia Governance Related to the Banks and Other Financial Institutions Act (BOFIA) in Nigeria - Munubiyyah Sani Jibrin; Nura Ahmad; Umar Musa Yakasai (Journal of Islamic Economic and Business Research, 2023)
A regulatory review of Islamic banking laws concept and practice in Nigeria under conventional banking regulatory laws need to be reviewed and investigated. Sharia Regulatory laws have provided sufficient laws and practices for Islamic Financial Institutions to be integrated into Nigeria's existing system of the non-interest bank and Islamic windows. In light of the above, establishing the Financial Regulation Advisory Council of Experts (FRACE), the Advisory Committee of Experts (ACE), the Sharia Advisory Board (SAB), and the Banks and Other Financial Institutions Act (BOFIA) to promote the Sharia Governance of Islamic Financial Institutions, businesses, and institutions in Nigeria. This employed cognate narrative and approach review to deduce and examine lacunae in the applicable laws and assess the scholarly perception of ethical financing in the Islamic Financial Institutions sector. The study employed Structural Equation Modeling (SEM). Consequently, the results revealed the positive relationship between the FRACE, ACE, SAB, and BOFIA in promoting regulatory and prudential assessment toward Sharia Governance of Islamic Financial Institutions in Nigeria. The application of laws and insufficient and inefficacious practice of its application generate an awkward practice of Islamic banking, and its windows in conventional banks and other Islamic financial Institutions are practically concerned and measured for Sharia suitability. Thus, establishment and regulatory laws will enhance Islamic Financial Institution practices and ensure equal treatment and great concern as conventional financial institutions in the country.